Betel nut chewing history is an independent prognosticator for smoking patients with locally advanced stage IV head and neck squamous cell carcinoma receiving induction chemotherapy with docetaxel, cisplatin, and fluorouracil. Issue 1 (December 2016) - Su, Yan-Ye; Chien, Chih-Yen; Luo, Sheng-Dean; Huang, Tai-Lin; Lin, Wei-Che; Fang, Fu-Min; Chiu, Tai-Jan; Chen, Yen-Hao; Lai, Chi-Chih; Hsu, Cheng-Ming; Li, Shau-Hsuan
Abstract Background Smoking and betel nut chewing are well-known risk factors for head and neck squamous cell carcinoma (HNSCC). Smoking is also a strong prognosticator for patients with locally advanced HNSCC receiving induction chemotherapy. Smoking with or without betel nut chewing is a common practice in Asia. However, little is known regarding whether betel nut chewing can serve as a prognostic factor for smoking patients with locally advanced HNSCC receiving induction chemotherapy. The aim of this study was to evaluate the prognostic impact of betel nut chewing in such patients receiving induction chemotherapy with docetaxel, cisplatin, and fluorouracil (TPF). Methods From January 2010 to December 2012, we retrospectively analyzed 162 smoking patients with locally advanced HNSCC who received induction chemotherapy with TPF at our institution. Background characteristics, including a history of betel nut chewing, were analyzed as potential prognostic factors. Results Among the 162 smoking patients, 131 patients (81 %) were betel nut chewers, while 31 (19 %) were non-betel nut chewers. One hundred fifty-six (96 %) were men, and 6 (4 %) were women. The median age was 53 years. The overall response rates to induction chemotherapy were 57 and 77 % in patients with and without betel nut chewing history, respectively (P = 0.038). The 2-year progression survival rates were 37 and 67 % in patients with and without betel nut chewing history, respectively (P = 0.004). The 2-year overall survival rates were 47 and 71 % in patients with and without betel nut chewing history, respectively (P = 0.017). Betel nut chewing history was independently associated with a poor response to induction chemotherapy, an inferior progression-free survival rate, and a poor overall survival rate. Conclusions Our results indicate that betel nut chewing history is independently associated with poor prognosis in smoking patients with locally advanced HNSCC receiving induction chemotherapy with TPF. Further investigation is warranted to explain this effect of betel nut chewing history on these patients' prognosis.